The Role of Peer Support as a Social Protective Factor for Adolescent Resilience with ADHD: Literature Review in a Positive Psychology Perspective - Badrina Alfi; Iriani Indri Hapsari; Yufiarti; Zarina Akbar (Department of Psychology, Faculty of Education, Universitas Negeri Surabaya, 2025)
Adolescents with Attention Deficit Hyperactivity Disorder (ADHD) often face complex challenges in their social relationships of rejection, including rejection from peers, stigma and difficulty in building meaningful friendships. However, some of them are able to show resilience in adapting positively in the midst of the social pressures they face. This study aims to explore the role of peer support as a social protective factor in building resilience of adolescents with ADHD through the perspective of Positive Psychology. This study uses a literature review method that refers to 20 selected articles in the range of 2015 – 2025, which are then analyzed thematically. The results of the review show that peer support contributes greatly to increased social acceptance, self-efficacy, emotion regulation, and minimizing the impact of stigma. Supportive peer relationships not only encourage adaptive coping strategies but also serve as a foundation for healthier psychosocial development, especially for adolescents with ADHD. The study also emphasizes the need for a shift from a deficit paradigm to a culturally sensitive strength, in order to maximize the resilience potential of adolescents with ADHD in their social contexts.